NUMERICAL ANALYSIS OF A COMPOSITE LEG PROSTHESIS - Gomes dos Santos, Joao Victor [UNESP]; Wong, Vincent [UNESP]; Neto, Vicente Gerlin; Paschoarelli, Luis Carlos [UNESP]; Reis Pereira, Marcos Antonio dos [UNESP]; Fortulan, Carlos Alberto; Foschini, Cesar Renato; Gomes, JFS; Meguid, S. A. (Inegi-inst Engenharia Mecanica E Gestao Industrial, 2018)
This work consists on analysing the behaviour of a transtibial prosthesis developed with a new composite material of polymer matrix and bamboo reinforcement. The analysis developed was a static analysis using the finite element method, considering the tensions generated by the weight of the patient using an FEA software (NASTRAN IN CAD 2015 and AUTODESK INVENTOR 2015). The development of this study will provide information on the elements that suffer the highest concentration of stresses.
Keywords: biocomposites; Finite Element Method; prosthesis; bamboo